Heat transfer and fluid flow characteristics in microchannels heat exchanger using nanofluids: A review - Mohammed, H.A.; Bhaskaran, G.; Shuaib, N.H.; Saidur, Rahman (Elsevier, 2011)
Advancement in the electronics industry led to the development of microscale heat transfer devices which offered high heat transfer coefficient in a compact size. Nevertheless, the heat transfer characteristics were limited by the heat transfer fluids that were used. The recent development of nanotechnology led to the concept of using suspended nanoparticles in heat transfer fluids to improve the heat transfer coefficient of the base fluids. The amount of research done in this particular field is fairly new and limited. Most studies done on microchannel devices and nanofluids recently have reported enhanced heat transfer capabilities and results that challenge traditional theories and limitations on heat transfer devices and fluids. Several important aspects of microchannel heat exchangers that affect the performance such as channel geometry, fluid inlet and outlet arrangement, type of construction were discussed together with the reported findings from experimental, numerical and theoretical literatures. This review also focuses on the important aspects of nanofluids such as types, properties and heat transfer characteristics and limitations towards the application of nanofluids. Apart from that, a comprehensive review on the work done regarding to heat transfer and fluid flow characteristics in microchannels heat exchanger using conventional fluids as well as nanofluids is also described.